Trends in Over-the-top (OTT) Video Services in Asian Countries- A Systematic Review of Literature - Saggu, Jasleen Kaur; Mohan, Tarannum (The journal of contemporary issues in business and government, 2023)
Consumer media consumption habits have changed significantly as a result of the introduction of over-the-top video (OTT) services. While the market for streaming services in the West seems to be saturated, Asia still has room for growth. Asia is a complex market with a mix of international, regional, and local streaming services, with ownership often coming from a telecoms player, media corporation, or broadcaster. Despite the immense growth of OTT video services, there still has been very limited research done in this area. The purpose of the study is to investigate the current trends in OTT research by synthesizing the available literature and to identify the research areas in the context of OTT that could be pursued in the future. This study provides a systematic review of 26 research articles published on OTT video services between 2017 to 2022 in the context of Asian countries. It classifies the literature in terms of years, countries, theories and models used or variables identified, research methods, findings and implications or suggestions. The study implies that the future research on OTT should explore the perspective of service providers anad regulatory bodies as well.